The satanic verses - Rushdie, Salman ([Place of publication not identified] Vintage, 1998)
A hijacked jumbo jet blows apart high above the English Channel. Two figures, Gibreel and Saladin, are washed up on an English beach. Soon curious changes occur -Gibreel seems to have acquired a halo, while Saladin grows hooves and bumps at his temples.
Angel Gibreel -- Mahound -- Ellowen Deeowen -- Ayesha -- City Visible but Unseen -- Return to Jahilia -- Angel Azraeel -- Parting of the Arabian Sea -- Wonderful Lamp.
First published in Great Britain in 1988.